2021
DOI: 10.5210/fm.v26i5.11693
|View full text |Cite
|
Sign up to set email alerts
|

Control by infrastructure: Political ambitions meet technical implementations in RuNet

Abstract: Discourse about sovereignty and Internet in Russia is predominantly focused on control of harmful content and information and its negative influence on the political regime and society. However, content control is not the only way to exercise sovereignty over digital media and the Web. Recently, the Russian government started to realize that without controlling Internet infrastructure, most strategies to filter and block Web sites and services are wasted. In the past five to seven years, Russia invested a lot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Moreover, those applications of the database that are particularly relevant for indirect media control (algorithmic downranking of flagged domains) are considered company secrets. Recently, transparency concerns have also been expressed regarding website blocking (Stadnik, 2021). As was mentioned above, the Russian Internet Sovereignty Act enables website blocking through state-controlled deep packet inspection filters which may turn it into a black box.…”
Section: Discussion: Implications and Possibilities For Misusementioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, those applications of the database that are particularly relevant for indirect media control (algorithmic downranking of flagged domains) are considered company secrets. Recently, transparency concerns have also been expressed regarding website blocking (Stadnik, 2021). As was mentioned above, the Russian Internet Sovereignty Act enables website blocking through state-controlled deep packet inspection filters which may turn it into a black box.…”
Section: Discussion: Implications and Possibilities For Misusementioning
confidence: 99%
“…The technical obstacles Roskomnadzor encountered in putting in place effective website blocking (Ermoshina & Musiani, 2021;Stadnik, 2021) have led to the restructuring of Russian internet governance through the Russian Internet Sovereignty Act (2019). This law transferred the implementation of website blocking from ISPs to the state.…”
Section: Russian Internet Governance and Media Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…She has concluded that all these methods are being implemented in Russia and that the Russian government seeks to provide "national security at any price" (Stadnik, 2021a, p. 162), to a large extent ignoring the interests of private stakeholders. In her other paper, Stadnik (2021b) examined four attempts of the Russian government to exercise control over information flows via internet infrastructure, including a blacklist to filter internet content, the law on "sovereign RuNet," the failed attempt to ban the messenger app Telegram in the country, and a list of "socially significant websites" that could potentially be used as a "white list" of accessible internet resources. She concluded that these measures "do not work as the government would wish" (Stadnik, 2021b) and that content filtering leads to, among other things, undesirable side effects for the whole network.…”
Section: The Russian Case: From An Underregulated Internet To Digital Sovereigntymentioning
confidence: 99%